PENGARUH MODEL PBL BERBANTU MEDIA PAPAN PECAHAN TERHADAP UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA KELAS II SDN PEDURUNGAN LOR 02 - Niken Ayu Kartika Sari; Duwi Nuvitalia; Monica Ratih Purwaningrum; Ikha Listyarini (Jurnal Bionatural, 2024)
Abstract This research aims to analyze the influence of the Problem Based Learning learning model assisted by fraction board media on the numeracy abilities of class II students at SDN Pedurungan Lor 02. This research uses a quantitative experimental design with a one group pretest-posttest design. The data collection technique uses a written test with indicators of numeracy ability, namely; 1) using various kinds of numbers and symbols related to basic mathematics, 2) analyzing information displayed in various forms, and 3) interpreting the results of this analysis to predict and make decisions. The research location was in class II at SDN Pedurungan Lor 02. The sample in this study was 30 students using saturated sampling techniques. And using data analysis in the form of data normality tests, simple linear regression tests. The results of this research show that a simple linear regression test obtained a tcount value of 6.902 > ttable 2.048, so the application of the Problem Based Learning learning model assisted by fraction board media (X) has an influence on students' numeracy abilities (Y). Based on the research results, it can be concluded that there is an influence of the Problem Based Learning learning model assisted by fraction board media on students' numeracy abilities at SDN Pedurungan Lor 02.  Keywords : Problem Based Learning, Fraction boards, Numeracy Ability